Industry history: Its concepts and methods (2018)
he second decade of the 21st Century seems to be witnessing a turn away from globalization. A buzzword for the past several decades, it is now being supplanted with a dramatic surge in discussion of anti-globalism in world politics. This backing away from the global reveals how fundamentally people had been affected both by the reality and the notion of globalization. The global integration of the market delivered a remarkable expansion of the world economy and the improvement of life in many parts of the world. Although it seemed to offer a promising pathway to overcome nationalism, it has actually provoked a fundamental concern within nations for the future of their economic life and identity. The world-wide technology transfer and the diffusion of knowledge made possible the rapid catch-up by “the rest” (Amsden 2001), turning around the few centuries long trend of “Great Divergence” (Pomeranz 2000). While integration promoted development in some parts of the world, it also caused citizens in once dominant nations to fear they would face competition from lower cost labor and production from the less developed nations. Likewise, global integration of the capital market accompanied the increased inequality in many nations and left many people behind. The transformation of global value chains and the enhanced mobility of corporate activities triggered concerns about the de-coupling between the interest of globalized firms and the priority of local economies. Intensified mobility of a skilled workforce also triggered dread of competition with immigrants in rich countries and, at the same time, led poor economies to fear a brain drain of needed skilled workers.